Digital sats eller digital satsing? - Ore, Christian-Emil; Tvedt, Lars Jørgen (Nordiske Studier i Leksikografi, 2006)
Presentation or content? The Unit for Digital Documentation at the University of Oslo has been making dictionary writing systems (DWS) for more than ten years. In this paper we will present some of our ideas on how a modern DWS should deal with the source material, other dictionaries and cross references inside the dictionary, and what implications this will have on the implementation of such a system.